1990
DOI: 10.1021/bi00494a017
|View full text |Cite
|
Sign up to set email alerts
|

2D NMR and structural model for a mitochondrial signal peptide bound to a micelle

Abstract: The 19 amino acid signal peptide of rat liver aldehyde dehydrogenase, possessing a lysine substitution for an arginine and containing 3 extra amino acid residues at the C terminus, was studied by two-dimensional NMR in a dodecylphosphocholine micelle. In this membrane-like environment, the peptide contains two alpha-helical regions, both of which are amphiphilic, separated by a hinge region. The helix located closer to the C terminus is more stable than is the helix located near the N terminus. This suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
71
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 41 publications
11
71
1
Order By: Relevance
“…From these data, it appears that the peptide has a helix-breakhelix motive, a motif that has been reported for other presequence peptides as well [9,11,13]. These conclusions extend a previous 2D NMR study on p25 [8], in which it was shown that p25 bound to DPC micelles has one helix at the N-terminus followed by a relatively structureless C-terminal half, of which the authors stated that the structure remained to be defined.…”
Section: Moreover the Medium Range Hu(i)-hfl(i+3) Ha(i)-nh(i + 3)supporting
confidence: 85%
See 1 more Smart Citation
“…From these data, it appears that the peptide has a helix-breakhelix motive, a motif that has been reported for other presequence peptides as well [9,11,13]. These conclusions extend a previous 2D NMR study on p25 [8], in which it was shown that p25 bound to DPC micelles has one helix at the N-terminus followed by a relatively structureless C-terminal half, of which the authors stated that the structure remained to be defined.…”
Section: Moreover the Medium Range Hu(i)-hfl(i+3) Ha(i)-nh(i + 3)supporting
confidence: 85%
“…More detailed information on the conformation of several synthetic mitochondrial presequence peptides in membrane-like environments was obtained using high-resolution 2D NMR. The peptide, corresponding to the presequence of yeast cytochrome oxidase subunit IV, also denoted as p25 [8], as well as the presequence peptide of rat liver aldehyde dehydrogenase [9] and a mutant peptide lacking the flexible linker comprising residues 11-13 [10], were investigated in the presence of DPC micelles. The presequence peptide of Ft-ATPase fl-subunit [11] and the non-cleavable N-terminal targeting extensions of rat rhodanese, rat 3-oxalyl-CoA thiolase [12] and rat chaperonin 10 [13] were analysed in aqueous trifluorethanol solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The application of multidimensional NMR to non-water-soluble peptide segments from integral membrane proteins is nevertheless limited. Most investigations have been performed with N-terminal and C-terminal signal peptides (Bruch et al, 1989;Karslake et al, 1990;Rizo et al, 1993;Wang et al, 1993;Chupin et al, 1995;Yamamoto et a]., 1990;Wolff et al, 1994). The structures of gramicidin A, mellitin and alamethicin have been determined in bilayers of phosphatidylcholine (PtdCho) and micelles of dodecylphosphocholine or SDS (Inagaki et al, 1989;Ketchem et al, 1993;Franklin et al, 1994;Okada et al, 1994).…”
mentioning
confidence: 99%
“…In addition, the very hydrophobic peptide segments usually will not dissolve in organic solvents or will not adopt the structures that are relevant to a cell membrane. For these reasons, detergent-micellar solutions are used to solubilize peptides where the hydrophobic core of the micelle is assumed to mimic that of a lipid bilayer (Inagaki et al, 1989;Karslake et al, 1990;Rizo et al, 1993;Franklin et al, 1994;Chupin et al, 1995;Gilbert and Baleja, 1995). Even the use of micelles in these studies may introduce non-biological properties, since the lipid packing around the peptides may differ from that in the biological membrane.…”
mentioning
confidence: 99%
“…The mammalian precursors, aldehyde dehydrogenase (pALDH) 1361, rhodanese, and 3-oxoacyl-CoA thiolase (thiolase) [38] contain signal sequences in which the structure has been determined by twodimensional NMR. The presequence of pALDH forms a helixlinker-helix [36]. Linker-deleted ALDH consists of the presequence of ALDH with a deletion of the flexible linker, residues RGP.…”
Section: Resultsmentioning
confidence: 99%